تعليمية الخط العربي في المراحل الصفية الأولى - الدكتور/ نجيم حناشي (Journal of Calligraphy, 2023)
The educational reality that falls during the primary period is the basic rule that build the educational status for the pupil. In fact, it is during the period that pupils learn the basics of the Arabic calligraphy, which is the main branch of the Arabic language. Moreover, this skill helps à lot the pupil in character building and Development. In fact, this is the title of our study. In this research: At which extend can we activate the education of the Arabic Calligraphy through the first grade stages? Some secondary questions can derive from this title: - How do we teach the Arabic calligraphy during the primary period? What are the obstacles that teachers meet to transmit calligraphy to the learner? What are the obstacles the learners face during learning the Arabic calligraphy? What me the suggested solutions for this problems and obstacles. We have based our analysis on the descriptive and analytical method for it is suitable for this kind of subject to describe an interpret this phenomenon يعدّ الواقع التعليمي الذي يندرج في المراحل الصفّية الأولى (المرحلة الابتدائية) بمثابة القاعدة الأساسية التي يبنى عليها المستوى التعليمي للتلميذ حيث يتلقى خلالها مختلف قواعد الخط العربي باعتباره فرعا أساسيا من فروع اللغة العربية، إلى جانب مساهمة هذه المهارة في بناء شخصية التلميذ وتنميتها والإفادة منها. وعليه فإن إشكالية هذه الدراسة تتمحور حول: إلى أيّ مدى يمكن تفعيل تعليمية الخط العربي في المراحل الصفية الأولى؟ ويمكننا إدراج تحت هذه الإشكالية تساؤلات فرعية متعددة تتمثل في: - كيف يتم تعليم الخط وتعلمه في المرحلة الابتدائية ؟ - ماهي الطرائق المتبعة في ذلك؟ - ماهي الصعوبات التي يواجهها المعلّم في إيصال الخط للمتعلم؟ - وفي المقابل ماهي الصعوبات التي يواجهها المتعلم؟ - ماهي الحلول المقترحة لمعالجة مثل هذه المشكلات و الصعوبات؟ وقد اعتمدنا في تحليلنا على المنهج الوصفي التحليلي، كونه ملائما لطبيعة هذا الموضوع، من حيث وصف الظاهرة وتفسيرها.